Laser interstitial thermal therapy for treatment of cerebral radiation necrosis. (15th July 2020) - Hong, Christopher S.; Beckta, Jason M.; Kundishora, Adam J.; Elsamadicy, Aladine A.; Chiang, Veronica L.
Abstract: Radiation necrosis is a well described complication after radiosurgical treatment of intracranial pathologies – best recognized after the treatment of patients with arteriovenous malformations and brain metastases but possibly also affecting patients treated with radiosurgery for meningioma. The pathophysiology of radiation necrosis is still not well understood but is most likely a secondary local tissue inflammatory response to brain tissue injured by radiation. Radiation necrosis in brain metastases patients may present radiographically and behave clinically like recurrent tumor. Differentiation between radiation necrosis and recurrent tumor has been difficult based on radiographic changes alone. Biopsy or craniotomy therefore remains the gold standard method of diagnosis. For symptomatic patients, corticosteroids are first-line therapy, but patients may fail medical management due to intolerance of chronic steroids or persistence of symptoms. In these cases, open surgical resection has been shown to be successful in management of surgically amenable lesions but may be suboptimal in patients with deep-seated lesions or extensive prior cranial surgical history, both carrying high risk for peri-operative morbidity. Laser interstitial thermal therapy has emerged as a viable, alternative surgical option. In addition to allowing access to tissue for diagnosis, thermal treatment of the lesion can also be delivered precisely and accurately under real-time imaging guidance. This review highlights the pertinent studies that have shaped the impetus for use of laser interstitial thermal therapy in the treatment of radiation necrosis, reviewing indications, outcomes, and nuances toward successful application of this technology in patients with suspected radiation necrosis.